2015
DOI: 10.1209/0295-5075/109/12001
|View full text |Cite
|
Sign up to set email alerts
|

Intense vacuum ultraviolet and infrared scintillation of liquid Ar-Xe mixtures

Abstract: Vacuum ultraviolet light emission from xenon-doped liquid argon is described in the context of liquid noble gas particle detectors. Xenon concentrations in liquid argon from 0.1 ppm to 1000 ppm were studied. The energy transfer from the second excimer continuum of argon (∼ 127 nm) to the second excimer continuum of xenon (∼ 174 nm) is observed by recording optical emission spectra. The transfer almost saturates at a xenon concentration of ∼10 ppm for which, in addition, an intense emission in the infrared at a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 21 publications
4
45
0
Order By: Relevance
“…The shape of averaged waveform has a simple hump structure described by two processes: transfer of excitation from Ar * 2 to Xe atoms with formation of Xe * 2 excited molecules (2.2) and the subsequent decay of those. Note, that there is an infrared emission from de-excitation of (ArXe) * molecules described in papers [17,32]. However, this infrared component is invisible with our PMT.…”
Section: Re-emission Of the Fast Component Of Lar Scintillationmentioning
confidence: 74%
See 2 more Smart Citations
“…The shape of averaged waveform has a simple hump structure described by two processes: transfer of excitation from Ar * 2 to Xe atoms with formation of Xe * 2 excited molecules (2.2) and the subsequent decay of those. Note, that there is an infrared emission from de-excitation of (ArXe) * molecules described in papers [17,32]. However, this infrared component is invisible with our PMT.…”
Section: Re-emission Of the Fast Component Of Lar Scintillationmentioning
confidence: 74%
“…This improves position reconstruction since the re-emission occurs in the point of interaction.It was shown that gaseous xenon doped in LAr works as a volume-distributed WLS shifting the wave length from 128 nm to around 175 nm [14][15][16]. Currently several groups are studying its wavelength shifting parameters and the properties of the LAr+Xe mixture [17][18][19][20]. As shown previously [21], Xe doped in small concentrations (up to 260 ppm by mass) re-emits only the slow component of LAr scintillation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Argon does have a "third continuum" in its emission spectrum that produces some light between the UV and IR [13] and no study has completely ruled out this mechanism in xenon. However, a study on xenon-doped argon [14] shows no scintillation between the UV and IR. Assuming the same holds true tering is neglected for photons with wavelengths greater than 436 nm as in those wavelengths the scattering length is much larger than the detector sizes simulated here.…”
Section: Index Of Refractionmentioning
confidence: 97%
“…The excited N * 2 (C) states can be quenched in collisions with Ar and N 2 species in reaction (10) and (12); in particular reaction (10) competes with reaction (8) Fig. 1: Energy levels of the lower excited and ionized states relevant to the ternary mixture of Ar doped with Xe and N2 in the two-phase mode; these are shown for gaseous Ar [32], gaseous N2 [33,34], gaseous Xe [32], liquid Ar [19,[35][36][37][38] and Xe in liquid Ar [22,38]. For N2, the vibrational levels of the C 3 Πu, B 3 Πg and A 3 Σ + u molecular states, as well as the dissociation levels (N+N), are also shown (except those of the ground state X 1 Σ + g ).…”
mentioning
confidence: 99%